Cardiac magnetic resonance patterns of left ventricular hypertrophy in aortic stenosis patients. (3rd October 2022) - R Santos, R; Abecasis, J; Maltes, S; Mendes, G S; Oliveira, L; Horta, E; Guerreiro, S; Freitas, P; Ferreira, A; Ribeiras, R; Andrade, M J; Cardim, N; et al.
Abstract: Background: Left ventricular (LV) hypertrophy is a known compensatory mechanism to pressure overload in aortic stenosis (AS) patients. However, by cardiac magnetic resonance (CMR) different patterns of LV adaptation are seen in this group of patients. Aim: To describe the patterns of LV adaptation (by CMR) and to analyze its structure and function indexes in AS patients referred for surgical aortic valve replacement (AVR). Methods: We prospectively studied 134 consecutive patients (age: 73y [IQR 68–77y], 49% men) with severe symptomatic AS - mean transaortic pressure gradient (AVmean): 61±1.5 mmHg; mean aortic valve area: AVA): 0.7±0.1 cm 2, referred for surgical AVR with no previous history of ischemic cardiomyopathy or other. All patients underwent electrocardiogram, 2D transthoracic echocardiogram (TTE) and cardiac magnetic resonance (CMR) before surgery for LV assessment and tissue characterization. Five patterns of LV structure were considered: normal ventricular structure (normal LV mass/volume ratio [M/V], normal LVMi and normal indexed LV end-diastolic volume (LVEDVi); concentric remodeling: increased M/V, normal LVMi; concentric hypertrophy: increased M/V and LVMi; eccentric hypertrophy: increased LVMi and LVEDVi, normal M/V and ejection fraction; and adverse remodeling: dilated left ventricle, increased LVMi and normal M/V in the context of an impaired ejection fraction. Echocardiogram and CMR structural and functional indexes were compared between these groups. Results: At baseline study, at CMR: mean LV indexed mass [LVMi]: 80.3±26.5 g/m 2 ; mean end-diastolic LV indexed volume [LVEDVi]: 84.4±24.5 mL/m 2 and median geometric remodeling ratio [M/V]: 0.95 g/mL [IQR 0. 81–1.08 g/mL]. Overall, 22% patients had normal LV structure, 30% concentric remodeling ventricular geometry, and two patients had an adverse remodeling pattern. LV hypertrophy was the most prevalent pattern and occurred in 48% of subjects (concentric 43%; eccentric 4%). In our cohort, the severity of AS (AVmean (p<0.001), LV function (LV ejection fraction [p<0.001] and Global longitudinal strain [p<0.001]), LV loading conditions (indexed left atrial volume [p<0.001] and E/e' ratio [p<0.001]) and NT-proBNP (p<0.001) were related to the pattern of LV structure (Table 1). Conclusions: In our cohort, AS patients presented several distinct patterns of LV remodeling. Disease severity, functional repercussion and loading conditions are distinct between them. Funding Acknowledgement: Type of funding sources: None.